Prevalence of Extended-Spectrum Beta Lactamase enzymes in clinical isolates of Enterobacteriaceae family - SM Moosavian; A Rezvanirad (مجله دانشگاه علوم پزشکی گرگان, 2016)
Background and Objective: Extended-Spectrum Beta Lactamase enzymes (ESBLs) are the most important factor for antimicrobial resistance in Enterobacteriaceae The resistance to beta-lactam antibiotics is the main problem in the bacterial infections therapy. This study was done to determine the prevalence of Extended-Spectrum Beta Lactamase enzymes in clinical isolates of Enterobacteriaceae family.